Hypocholesterolaemia and non-cardiovascular disease: metabolic studies on subjects with low plasma cholesterol concentrations. Issue 6378 (21st May 1983) - Marenah, C B; Lewis, B; Hassall, D; La Ville, A; Cortese, C; Mitchell, W D; Bruckdorfer, K R; Slavin, B; Miller, N E; Turner, P R; Heduan, E
Abstract : Some epidemiological studies have suggested an inverse relation between serum cholesterol concentration and mortality from cancer. Two hypotheses that might explain such a relation were investigated. To assay potentially deleterious effects of hypocholesterolaemia on cell membranes the lipid content and fluidity of blood mononuclear cells were measured in healthy male volunteers with a wide range of serum cholesterol concentration (3.2-10.0 mmol/l (124-387 mg/100 ml)). Fluidity, unesterified cholesterol content, and the ratio of cholesterol to phospholipid were unrelated to serum cholesterol and to low density lipoprotein cholesterol concentrations. Similar measurements were made on fibroblasts and mononuclear cells incubated with a range of concentrations of low density lipoprotein; fluidity was altered only at extremely low concentrations, suggesting that changes in cell membranes are unlikely to occur at serum cholesterol concentrations attainable by dietary or drug treatment of hyperlipidaemia. In the same population direct relations were confirmed between low density lipoprotein concentration and plasma concentrations of retinol and beta carotene. This is compatible with the suggestion that an association between low cholesterol concentration and cancer may be secondary to a relation between low retinoid concentrations and cancer.